Study of the complexation of copper ( II ) with 2,6-dithiol-phenol and hydrophobic amines - Ismayilova Shahnaz Y.; Hajıbayli Tahira A.; Huseynova Nazile S.; Zaynalova G.R.; Abdullayeva Elgul A. (Reviews of Modern Science, 2024)
The stoichiometry of the studied complexes was determined by the methods of equilibrium shift and relative yield. Shown in Fig. 3 data show that the ratio of components in the composition of RLC C u (II): DTP: Am. Using the Nazarenko method, it was established that the complexing form of copper is C u 2+ . In this case, the number of protons displaced by it from one DTP molecule turned out to be equal to 1. In the IR spectra of the complex, an intense absorption band appears in the region of 950-960 cm -1 , which is absent in the spectra of the reagent. This band is due to the stretching vibration of the metal-ligand bond. The disappearance of a pronounced band at 2580 cm -1 observed in the DTP spectrum and the appearance in the spectra of the complex of two absorption bands , one of which is shifted towards lower frequencies, indicates that one of the -SH groups is involved in the formation of the complex. The disappearance of the absorption band in the region of 3200-3600 cm -1 with a maximum at 3460 cm -1 shows that the hydroxyl group takes part in the formation of a bond with the metal. The detection of an absorption band at 2380 cm -1 indicates the presence of protonated aniline, and an absorption band at 1370 cm -1 indicates the presence of coordinated aniline.